Leadership for Health Equity - Sáenz Madrigal, María del Rocío (2023)
This presentation, delivered by Dr. Rocío Sáenz, explores leadership in public health with a focus on equity. It addresses systemic dimensions of the health context, including clinical, political, operational, and strategic aspects. The author highlights key qualities of effective leadership such as adaptability, innovation, respect, collaboration, and clear communication. Reflections are offered on female leadership, teamwork, emotional management, and the importance of separating personal, work, and domestic spheres. The approach is participatory, democratic, and results-oriented, promoting capacity building and collective action.